Basic Psychological Need Satisfaction, Recovery State, and Recovery Timing. Issue 2 (15th March 2018) - van Hooff, Madelon L. M.; Flaxman, Paul E.; Söderberg, M.; Stride, Chris B.; Geurts, Sabine A. E.
ABSTRACT: This study aimed to provide insight into recovery from work-related load effects by examining (a) whether basic psychological need (BPN) satisfaction during nonwork days facilitates recovery, (b) whether the effect of BPN satisfaction is stronger in case of an unfavorable initial recovery state, and (c) whether the association between BPN satisfaction and recovery is stronger on nonwork weekend days compared to nonwork weekdays. Data were collected across 7 consecutive days from 205 employees (39% shift workers). Fatigue and depressed mood were assessed as indicators of (failed) recovery. Multilevel analyses revealed that BPN satisfaction during nonwork days was related to improved recovery state. This association was stronger (a) if employees had experienced elevated fatigue on the preceding day and (b) on nonwork weekend days compared to nonwork weekdays.